Effects of Lactobacillus acidophilus NCFM and Bifidobacterium lactis Bi-07 Supplementation on Nutritional and Metabolic Parameters in the Early Postoperative Period after Roux-en-Y Gastric Bypass: a Randomized, Double-Blind, Placebo-Controlled Trial - Ramos, Marília Rizzon Zaparolli; de Oliveira Carlos, Lígia; Wagner, Nathalia Ramori Farinha; Felicidade, Ingrid [UNESP]; da Cruz, Magda Ramos; Taconeli, Cesar Augusto; Fernandes, Ricardo; Filho, Alcides José Branco; Campos, Antônio Carlos Ligocki (Springer Nature, 2021)
Abstract: Studies have suggested that Roux-en-Y gastric bypass (RYGB) causes changes in the intestinal microbiota composition and function due to anatomical and physiological modifications. The role of probiotic supplementation after bariatric procedures remains to be determined. Purpose: The aim of this study was to investigate the effects of Lactobacillus acidophilus NCFM and Bifidobacterium lactis Bi-07 supplementation on nutritional and metabolic parameters after RYGB. Materials and Methods: This is a randomized, double-blind, placebo-controlled clinical trial. Patients were assigned to receive either a probiotic supplement (FloraVantage®) or placebo for three consecutive months, beginning 7 days after surgery. Anthropometric and biochemical indexes were evaluated in the preoperative period and at the end of the study. Results: Following RYGB, serum 25-OH vitamin D increased in both groups compared to baseline; however, this increase was significant only in the probiotic group (p = 0.004). Vitamin B12 levels tended to be higher in the probiotic group compared to the placebo group (p = 0.063), and triglyceride levels showed a significant reduction in the probiotic group only (p < 0.001). In addition, a significant reduction was observed in the anthropometric parameters and glycemic profile (p < 0.05) in both groups. Conclusion: Probiotic supplementation after RYGB improves the vitamin and lipid profile.
Keywords: Bariatric surgery; Probiotics; Roux-en-Y gastric bypass